Accountants' Handbook, Sixth Edition (Book). - Tracy, John A.; Meyer, Philip E. (The Accounting Review, 1982)
Abstract Reviews the book " Accountants' Handbook," 6th ed., edited by Lee J. Seidler and D.R. Carmichael.